Gaya Humor dan Perilaku Cyberbullying pada Remaja - Aulia Triatmi Astharini Abdullah; Rohmah Rifani; Andi Nasrawati Hamid (Universitas Sulawesi Barat, 2022)
This study aims to determine the relationship between humor style and cyberbullying behavior among adolescents in Makassar City. The research population is the age range of 15-19 years. Respondents 420 SMP, SMA, and SMK students were obtained through the distribution of online questionnaires using google-form with the help of their school counselors. The humor style questionnaire was arranged based on the humor style dimensions of Martin (2003), namely self-enhancing, aggressive, affiliative, and self-defeating, while the cyberbullying behavior questionnaire was arranged based on three aspects of cyberbullying behavior by Lee, Abell, and, Holmes (2015), namely verbal/written bullying, visual/sexual bullying, and social exclusion. The results showed that there are two styles of humor that have a significant relationship with cyberbullying behavior in adolescents around Makassar City, namely the affialitive humor style and the aggressive humor style. Affiliative humor style has a significant negative relationship with cyberbullying behavior, aggressive humor style has a significant positive relationship with cyberbullying behavior. While the other two styles of humor, namely self-enhancing humor and self-defeating humor, did not show a significant relationship with cyberbullying behavior.